The little dippers: transits of star-grazing exocomets?. Issue 3 (3rd December 2018) - Ansdell, M; Gaidos, E; Jacobs, T L; Mann, A; Manara, C F; Kennedy, G M; Vanderburg, A; Kenworthy, M; Hirano, T; LaCourse, D M; Hedges, C; Frasca, A
ABSTRACT: We describe EPIC 205718330 and EPIC 235240266, two systems identified in the K2 data whose light curves contain episodic drops in brightness with shapes and durations similar to those of the young 'dipper' stars, yet shallower by ∼1–2 orders of magnitude. These 'little dippers' have diverse profile shapes with durations of ≃0.5–1.0 d and depths of ≃0.1–1.0 per cent in flux; however, unlike most of the young dipper stars, these do not exhibit any detectable infrared excess indicative of protoplanetary discs, and our ground-based follow-up spectra lack any signatures of youth while indicating that these objects are kinematically old. After ruling out instrumental and/or data processing artefacts as sources of the dimming events, we investigate possible astrophysical mechanisms based on the light curve and stellar properties. We argue that the little dippers are consistent with transits of star-grazing exocomets, and speculate that they are signposts of massive non-transiting exoplanets driving the close-approach orbits.